Uma nova métrica baseada em oportunidades de transmissão para avaliação de estratégias de encaminhamento em redes veiculares - Guerber, Carlos Rafael (2020)
In ad hoc vehicle networks (VANETs), vehicle-to-vehicle (V2V) communication occurs opportunistically due to the frequent mobility of nodes and the intermittent contact time. In this scenario, assessing the efficiency of referral protocols by using existing resources on the network is an open challenge, given the different strategies adopted by such protocols for choosing the next step. Through the analysis of vehicle movement data, this work contributes to the analysis of the existence of transmission opportunities with the use of a single radio, its quantification and classification considering the opportunities as serial when a sending vehicle only has one opportunity to transmit and parallel opportunity when the issuer has two or more opportunities to transmit. Four different scenarios were evaluated, three with the real features of taxi mobility in the cities of Rome, San Francisco and Shanghai, and one with randomly generated features. Furthermore, the radio signal range was varied from 50 to 1,000 meters in the evaluated scenarios. In addition, the inventory analysis of the communication resources is done through three measures: data transmission rate, impact of overhead of the beacons, and efficiency of routing protocols – performed using the proposed OpTs metric. This paper discusses the impact on forwarding protocols for the appropriate use of this metric, and shows that this metric can be used to evaluate the efficiency of forwarding protocols or to improve the quality of resource consumption in ad hoc vehicular networks. This metric allows message forwarding protocols to assess whether they are able to use the maximum theoretical resources available regardless of the scenario assessed. For Rome, San Francisco or Shanghai, as the radio signal range increases, the maximum theoretical amount of resources also increases. The assessment also shows, for the three scenarios, that the overload of beacons does not have a significant impact on the total inventory of theoretical data available. When applying the metric OpTs in forwarding protocols that use different strategies to forward messages, it was possible to observe that each of these protocols consumes resources differently. The metric also allows to evaluate the general efficiency of each routing protocol in a VANET when measuring the percentage of resource that such protocol used during the interaction between the vehicles. With the application of the metric it is possible to obtain the efficiency of a routing protocol in relation to its consumption of resources.